(untitled) (The Strategic Review for Southern Africa, 2022)
The little Caribbean island of Cuba is again making headlines in the world. In South Africa, Cuba has generated controversy due to the South African government “farming in” Cuban doctors and other medical specialists as well as engineers. The South African government’s nomination of the Henry Reeves Emergency Medical Contingent for a Nobel Prize further incensed many in the country. Much of the controversy, this article argues, is a result of Cuba suffering an unresolved duality for South Africans: Cuba supported the ANC in exile during its anti-apartheid struggle and also fought with the then South African Defense Force during the border wars in Angola from 1975 to 1987. The publication in 2021 of Cuba and Africa 1959-1994: Writing an alternative Atlantic history, edited by Bonacci, Delmas and Argyriadis presents scholars a remarkable opportunity to place Cuba’s history with Africa and South Africa in a context different from the traditional Cold War dichotomy characterising much of Cuba’s relationship with Africa. The new volume on Cuba/Africa history, which is silent on Cuba/South Africa relations in particular, is not comprehensive nor does it claim to be. Consequently, it provides South Africa and southern Africa with a unique opportunity and model to address Cuba’s unresolved duality for South Africans and contribute to the development of an improved engagement and understanding of a complex relationship of significance to Cuba, South Africa and other African nations.